2016
DOI: 10.1002/j.0022-0337.2016.80.10.tb06206.x
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Impressions and Work Authorizations Submitted by Dental Students Supervised by Prosthodontists and General Dentists

Abstract: Preclinical fixed prosthodontics is taught by Department of Prosthodontics faculty members at Virginia Commonwealth University School of Dentistry; however, 86% of all clinical cases in academic year 2012 were staffed by faculty members from the Department of General Practice. The aims of this retrospective study were to quantify the quality of impressions, accuracy of laboratory work authorizations, and most common errors and to determine if there were differences between the rate of errors in cases supervise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 16 publications
1
8
0
Order By: Relevance
“…Over the audit period, the overall proportion of satisfactory working impressions and those with only minimal defects increased to 85% which is very encouraging and compares very favourably to many previous studies. 4,5,6,7,8,12,13,18 This paper reinforces the benefits of clinical audit and provides a contemporary benchmark from which further studies can be undertaken.…”
Section: Resultssupporting
confidence: 52%
See 3 more Smart Citations
“…Over the audit period, the overall proportion of satisfactory working impressions and those with only minimal defects increased to 85% which is very encouraging and compares very favourably to many previous studies. 4,5,6,7,8,12,13,18 This paper reinforces the benefits of clinical audit and provides a contemporary benchmark from which further studies can be undertaken.…”
Section: Resultssupporting
confidence: 52%
“…Deficiencies in the quality assurance process has been reported elsewhere. 18 The subsequent action plan (Table 5) sought not only to review the undergraduate teaching, but to focus on the quality assurance process. Illuminated magnifiers were provided for use on clinic and staff were asked to check all impressions with these magnifiers or loupes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Beier et al also found a high level of clinically acceptable impressions; of 1466 impressions evaluated in this University setting, only 3% were clinically unacceptable . Findings from another University suggest a similar low incidence of unacceptable impressions at 4% . None of these studies correlated the quality of the impressions to the clinical fit of the crowns made from these impressions.…”
mentioning
confidence: 99%